Investigation of silica-based TL media for diagnostic x-ray dosimetry - Amjad., Alyahyawi,; Zahariman, Siti Rozaila; Ahmad Shaharuddin, Siti Shafiqah; Sabtu, Siti Norbaini; A, Alsubaie; A, Alanazi; Eman, Daar; S.F, Abdul Sani; D.A, Bradley (Elsevier Limited, 2017)
We focus on the development of Ge-doped silica thermoluminescent dosimeters with sensitivity superior to that of the LiF (Mg,Ti) phosphors popularly used in x-ray diagnostic imaging dosimetry, typically in the form of the product TLD-100. Of interest are Ge-doped silica telecommunication fibres (SMF) and tailor-made doped photonic crystal fibres (PCFc), the latter Ge-doped or also co-doped with boron. The PCFs are formed of capillaries that at high temperatures and under vacuum are made to collapse inwards (PCFc), the internal walls fusing and generating strain-related defects. To-date, the fabricated PCFc-Ge-B, PCFc-Ge and (SMF) have been observed to provide TL yields which weight-for-weight are some 15, 10 and 2 × that of TLD-100. In present study we test the linearity of TL yield for x-ray doses from 0.1- to 10 mGy, use being made of an x-ray tube operated at 80 kVp, a value typically selected in chest radiography. For a dose of 10 mGy, a study of energy dependence has been conducted using x-ray tube potentials of 80 kVp 100 kVp, and 120 kVp, with inherent filtration 0.9 mm Al measured at 75 kVp, and total filtration of 2.8 mm Al at 80 kVp.